1H MR Spectroscopy in Gliomatosis: Is there a Sensitivity Issue? - M. Szewczyk-Bieda; A. K. Kanodia; G. Main; M. S. Eljamel (Case Reports in Radiology)
Objective. 1H MR spectroscopy (MRS) is widely performed for assessment of brain tumours and is considered a highly sensitive technique capable of differentiating benign from malignant conditions and tumour grading. Method. We present a case of a 69 year old woman who was suspected to have gliomatosis on MRI. Results. MRS performed using single voxel and chemical shift/multivoxel techniques was within normal limits. A repeat scan 6 months later showed progressive disease, and biopsy was performed that proved the diagnosis of glioblastoma. Conclusion. Normal MRS in a patient with suspicion of gliomatosis on MRI should not reassure clinicians into assuming a benign aetiology or a good prognosis in short term.